On particle dynamics near the singularity inside the Schwarzschild black hole and T-spheres - A. Radosz; A. V. Toporensky; O. B. Zaslavskii (European Physical Journal C: Particles and Fields, 2023)
Abstract The problem of the speed of the objects inside the Schwarzschild black hole is considered. The general result is that the value of the relative speed of the objects following their non-zero angular momentum trajectories, both of geodesic and non-geodesic character, when approaching the ultimate singularity, tends to the value of speed of light. There is only one exception when both objects move in the same plane and have parallel angular momenta. This outcome appears to have a deeper sense: it reflects the anisotropic character of the dynamics of interior of this particular black hole. The result in question means that near the singularity, collisions of two particles lead to an indefinitely large energy in the center of mass frame. Aforementioned properties have their counterpart in the phenomenon of an indefinitely large blueshift near the singularity. Thus the angular momentum of a particle turns out to be an important feature that affects the final behavior of particle near the singularity. Motivated by this fact, we generalize the Lemaître frame under the horizon in such a way that reference particles themselves have nonzero angular momentum. Our results apply not only to the Schwarzschild singularity but also to other space-like ones for which the scale factor $$g→ ∞ $$ g → ∞ . We also analyze another type of singulairites for which the circumference radius vanishes but g remains finite.